Chemical Lecture Demonstrations: An Opportunity for Engagement through Collections, Instruction, and Reference. Issue 4 (2nd October 2017) - Hubbard, David E.
ABSTRACT: Chemical lecture demonstrations have been used as a pedagogical tool since at least the founding of chemistry as a discipline in the 1600s. This paper describes how science librarians can engage chemistry faculty and students through chemical lecture demonstrations. This paper describes chemical lecture demonstrations–including history and efficacy–and discusses how science librarians can engage chemistry faculty and students through collections, instruction, and reference in support of this pedagogy. In addition to outlining a research guide and lesson plan for chemical lecture demonstrations, this paper identifies chemical lecture demonstration monographs found in WorldCat® and analyzes the holdings of those monographs within the thirty-six-member Greater Western Library Alliance (GWLA) consortium.